Deriving green competitive advantage in the SMEs: A sustainable firm performance perspective - Abdul Samad Dahri; Ummi Naiemah Binti Saraih; Junaid Rehman; Anas A. Salameh; Fatuma Namisango (Sustainable Futures)
The role of SMEs is pivotal in driving the global economies. These represent 90 % of the business firms and provide over 50 % of the employment globally. Owing to an ever-increasing environmental consciousness, the manufacturing SMEs, particularly in the developing economies, have undergone strategic transformations by incorporating green capabilities into their production processes. Given the widespread environmental issues faced at the global landscape, especially the challenges encountered by the SMEs of the developing countries like Pakistan, it is important to investigate and address these issues in a sustainable manner. Therefore, this research investigated the collective influence of green resource capabilities such as Green Intellectual Capital (GIC), Green Entrepreneurial Orientation (GEO) and Green Innovation (GI) for deriving green competitive advantage in the SMEs of Pakistan. In this regard, the data were gathered from the Senior Managers who worked in 380 manufacturing SMEs of Pakistan and subsequently analyzed through Smart-PLS based SEM technique. The findings revealed a significant positive association between the examined variables. This research adds to the theory & practice of sustainability by suggesting the SMEs to adopt the empirically-tested green resource capabilities for achieving sustainable economic, social and environmental performance.